Hubungan Rugositas Terumbu Karang terhadap Struktur Komunitas Ikan Corallivor dan Herbivor di Perairan Pemuteran, Bali - Rafly, Nidzar Muhammad; Gede Astawa Karang, I Wayan; Widiastuti, Widiastuti (Journal of Marine Research and Technology, 2020)
Reef fishes are the highest number of organisms that can be found in coral reefs in which the abundance depends on the healthy of this ecosystem. Reef fishes are mainly consisted of corallivorous and herbivorous fish. Corralivorous fish feeds on coral polyps while herbivorous fish feeds on algae. Therefore these fishes are an important indicators in the resilience of coral reefs. Studies showed that its abundance is strongly correlated with reef’s conture (rugosity). Pemuteran waters is one of developing tourists attraction in the north Bali island. However, the data of reef fishes and coral reefs in Pemuteran waters remain limited. Therefore, this research aimed to study the reef` condition and rugosity in Pemuteran waters, also to examine the correlation between reefs fishes and reefs rugosity in this area. There were four stations according to purposive sampling method. Data of corallivorous and herbivorous fishes were collected by using the underwater visual census with a 40 m 2  transect. Reef rugosity index were determined by using chain transect method. Results showed that reef rugosity in Pemuteran waters was in the medium to high category. Reef rugosity has strong correlation with the total abundance and diversity of corallivorous fishes. However, reef rugosity was only strong correlated with the total abundance but not with the diversity of herbivorous fishes.